Buttock Augmentation Using Doppler Ultrasound-guided Cannulation for Patient Safety - Luis F. Reyes, MD; Nicole G. Echeverry, MD; Hugo A. Aguilar, MD; Juan M. Velasco, MD; Brian Ramírez, MD, MSc, PhD(c); Silvia Villabona, MD; Hector M. Serrano, MD; Agustina Varela, BA (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Augmentation gluteoplasty performed through autologous fat grafting is a surgical technique that volumizes the buttock and shapes the gluteal region according to the patient’s expectations, but it is one of the most dangerous aesthetic surgical procedures due to the high rate of the complication and mortality. The aim of the study was to assess the safety of subcutaneous gluteal fat grafting using ultrasound-guided cannulation. Methods:. A retrospective study of the clinical outcomes of gluteal augmentation with Doppler ultrasound-assisted fat grafting was conducted. The medical records of 177 patients who underwent gluteal augmentation between February and May 2024 were analyzed. Results:. In a sample of 177 patients who received gluteal fat grafting, we found that the visualization of perforating arteries had a median of 9 arteries (interquartile range: 2) per buttock. Distribution by quadrants varied among patients. The use of Doppler ultrasound-guided fat grafting was shown to be safe; related complications included 5 patients with hematomas, 2 with seromas, and 1 with suture dehiscence; no cases of infection, deep vein thrombosis, pulmonary embolism, or death were reported. Conclusions:. Subcutaneous gluteal lipoinjection with Doppler ultrasound indirect vision is a procedure that meets patient safety standards. It allows visualization of the tissue where the fat is grafted, reducing the risk of developing thrombotic events by identifying risk structures such as the intramuscular plane and vascular structures. Achieving a good aesthetic result and a low complication rate requires prior training in the use of ultrasound specifically for gluteal lipoinjection using Doppler.